Effect of Peripartum Supplementation of Rumen Protected Choline and Rumen Protected Fat on Energy Status, Insulin, IGF-1 and Postpartum Fertility in Gir Cows - Chavda, Miteshkumar R.; Savsani, Harish H.; Gadariya, Mahesh R.; Vala, Karsan B.; Dhami, Arjan J.; Karangiya, Vijay K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The experiment was carried out on 24 advanced pregnant Gir cows in their first to third lactation to study the effects of supplementing  rumen protected choline (RPC) and rumen protected fat (RPF) alone and in combination on their blood glucose, plasma insulin and  IGF-1 profile, and postpartum fertility. The cows were divided equally into four treatment groups (n = 6 each), T1 (control), T2 (RPC),  T3 (RPF) and T4 (RPC and RPF) on the basis of parity, body weight and previous lactation yield. In T1 group, cows were fed with basal diet to meet  their nutrient requirement as per Indian Council of Agricultural Research (ICAR) (2013) feeding standards. In T2, each cow was supplemented  with RPC @ 45 g/day, in T3 with RPF @ 80 g/d and in T4 with RPC @ 45 g/day + RPF @ 80 g/d along with basal diet of T1, starting from 30 days  before expected date of calving to 60 days postpartum. Concentrations of blood glucose, plasma insulin and IGF-1 studied at monthly interval  revealed drop in values around day 30 and 60 postpartum with significant differences in both the hormones. Supplementation of RPC and  RPF alone or in combination had no significant effect on blood glucose and plasma insulin levels, overall or at any period, except on day 60  postpartum where glucose was significantly higher in RPF group. Plasma concentration of IGF-1 was significantly (p
Keywords: Energy status; Gir cows; Plasma insulin; Postpartum fertility; Rumen protected choline; Rumen protected fat